Drivers of capital structure in Malaysian Real Estate Investment Trust Funds (M-REITs) - Abdul Rahim, Norhuda; Mohd Shawal, Nor Aishah; Ali, Muhammad Hafiz (Universiti Teknologi MARA (UiTM) Negeri Sembilan, 2021)
This study investigates drivers of capital structure decisions of Malaysian Real Estate Investment Trust Funds (M-REITs) using 121 observations from 15 REITs companies listed in the Bursa Malaysia during 8 years study period of 2011 to 2018. Employing the panel data regression model, the result indicates that operating risk is significantly negatively related to leverage suggesting that M-REIT firms with higher uncertainty of earnings opt for low leverage as it reduces their risk of bankruptcy. Consistent with pecking order theory, profitability is reported to have significantly negatively related to leverage implying that M-REITs with higher (lower) profits have lower (larger) debt albeit this industry is expected to have low retained earnings. Contrary to the trade-off theory, the asset tangibility is significantly negatively related to leverage indicating that M-REITs with higher fixed assets opt for lower debt. The uniqueness of M-REIT regulation could be the justification for this result.